Impact of titanium dioxide nanoparticles on intestinal community in 2, 4, 6-trinitrobenzenesulfonic acid (TNBS)-induced acute colitis mice and the intervention effect of vitamin E. Issue 3 (13th January 2021) - Gao, Yanjun; Li, Tingyu; Duan, Shumin; Lyu, Lizhi; Li, Yuan; Xu, Lin; Wang, Yun
Abstract : TiO2 NPs cause microbiota disorders and inflammation risks in healthy mice, but regulate gut microbiota and mitigate colitis symptoms in the TNBS-induced colitis mice, and the effect is independent of the ROS induction capability of TiO2 NPs. Abstract : Titanium dioxide nanoparticles (TiO2 -NPs) are widely applied as additives in foods due to their excellent whitening and brightening capability. Although the toxicity and antibacterial activity of TiO2 -NPs have been extensively studied, their impact on the gut microbiota in vivo still remains unclear, especially in animals with gastrointestinal disorders. In the present study, healthy mice and TNBS-induced colitis mice were administered with TiO2 -NPs (38.3 ± 9.3 nm) orally at a dose of 100 mg per kg bw daily for 10 days to study the impact of TiO2 -NPs on the gut microbiota and colitis development. Moreover, the mechanism of TiO2 -NPs on the gut microbiota was also discussed when the colitis mice were additionally administered with vitamin E to remove ROS. Changes in the microbiota community structure and gut-associated function prediction were analyzed through bioinformatics. The result showed that the oral administration of TiO2 -NPs mitigated colitis symptoms by reducing the DAI and CMDI scores and TNF-α level. Furthermore, 16S rDNA sequencing analysis showed that the structure and function prediction of gut microbiota could be modified in healthy mice and colitis mice after exposure to TiO2 -NPs, but the opposite physiological effect occurred since the dominant flora varied in these two groups. Moreover, vitamin E intervention did not change the effects of TiO2 -NPs on the microbiota community structure and gut-associated function, which indicates that the mechanism of the biological effects of TiO2 -NPs on the gut microbiota may not be associated with their ability to induce the generation of ROS. In summary, our work firstly found that TiO2 -NPs could regulate the gut microbiota of colitis mice and participate in the mitigation of TNBS-induced acute colitis, and the capability of TiO2 -NPs to induce the generation of ROS inducement did not contribute to this process.